Exploring Global Research Trends on the Integration of Information Technology in Pragmatic Studies: A Bibliometric Analysis - Haristiani, Nuria; Al Husaeni, Dwi Novia; Judiasri, Melia Dewi; Herniwati, H. (Bumi Publikasi Nusantara, 2025)
This study aims to explore global research trends on information technology integration in pragmatics studies through a bibliometric approach. Data were collected from the Scopus database over the past decade (2015–2024), resulting in 30 documents being analyzed. The analysis included document distribution based on publication type, institutional affiliation, author's country of origin, and keyword mapping using VOSviewer software. The analysis results show that most publications come from the United States, followed by the Russian Federation and the United Kingdom. The most productive institutions are RUDN University and Curtin University. The most dominant document type is scientific journal articles. Based on keyword co-occurrence analysis, three main clusters were identified: (1) technology integration approaches and processes, (2) evidence-based studies in educational and language contexts, and (3) communication applications and learning effectiveness. These findings provide a comprehensive overview of the research landscape in information technology integration in pragmatics and can serve as a strategic reference for academics and practitioners in designing more effective language learning innovations in the digital era.